Spatial Distributions of AQI, PM2.5, Relative Humidity, Speed, and Temperature in Twenty-Two Towns in Nigeria - Abulude, Francis Olawale; Al Shoumik, Baig Abdullah; Oluwafemi, Matthew Ojo; Arifalo, Kikelomo Mabinuola; Elisha, Jamok Jacob; Feyisetan, Abigail Oluwakemi (Iraqi Journal of Science, 2024)
The significant air pollution issue in Nigeria has sparked severe widespread fear. This research is a part of the effort to eliminate or reduce this threat. The research aimed to examine the distributions of Air quality index (AQI), Particulate matter with less than 2.5 µm diameter (PM2.5), Relative humidity (RH), Wind speed, and Temperature (temp) in nineteen (19) Nigerian states, including the Federal Capital Territory (FCT). To accomplish this, satellite data obtained from IQAir’s air quality monitoring platform for nineteen states and the Federal Capital Territory of Abuja between the 7th and 17th of October 2021 were used and statistically analyzed. The inverse distance weighting (IDW) interpolation method was applied to observe the spatial distribution of the data. The average AQI was 72.11, with minimum and maximum values of 26 and 17, respectively. The mean of PM2.5 was 28.71±13.7 µg/m3. The following meteorological average values were recorded: RH (62.43%), wind speed (6.96 m/s), and temperature (28.71oC). The AQI was between good and unhealthy, the PM2.5 was more than 17% (annual) and 52% (24 h), which is higher than World Health Organisation (WHO) limits, and the correlations between AQI, PM2.5 and meteorological parameters were weak. According to the data, PM2.5 was not distributed uniformly across the regions but varied spatially and temporally. It is advised that people check their local daily air pollution forecasts, avoid exercising outside, avoid working out in crowded areas, and use less energy at home to prevent an increase in AQI. It is recommended to monitor and maintain the air quality and minimize harmful anthropogenic activities to mitigate the threat.